Sexual dimorphism in morphognostic features of the inhabitants of the island of Palue - Josef Glinka, Josef Glinka (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1984)
The island of Palue belongs to the Lesser Sunda Islands, north of the island of Flores. The data given here arc of 526 men and 296 women. Nine features are presented: 1. the hairform, 2. the position of the aperture of the palpebra, 3. the epicanthus, 4. the size of the aperture of the mouth, 5. the thickness of the lips, 6. the profile of the forehead, 7. the profile of the nose, 8. the profile ofthe upper integ-umental lip, and 9. the prognathism. According CO the 12 >3 test only the 1st,the 4th, the 6th and the 7th features are significantly dimorphic. According to the chi-square test in contingency tables, besides this four, also the 2nd, the 8th and the 9th features could be accepted as dimorphic with the risk of P = 0.03, P 0.01 and P 0.056 respectively.Key Words: Indonesia - Lesser Sunda Islands - Palue - sexual dimorphism - morphognosric